Ischemia-reperfusion Injury in Allogeneic Liver Transplantation: A Role of CD4 T Cells in Early Allograft Injury. Issue 9 (19th August 2021) - Kageyama, Shoichi; Kadono, Kentaro; Hirao, Hirofumi; Nakamura, Kojiro; Ito, Takahiro; Gjertson, David W.; Sosa, Rebecca A.; Reed, Elaine F.; Kaldas, Fady M.; Busuttil, Ronald W.; Kupiec-Weglinski, Jerzy W.; Zhai, Yuan
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: A major discrepancy between clinical and most experimental settings of liver ischemia-reperfusion injury (IRI) is the allogenicity. Methods: In the current study, we first established a murine model of allogeneic orthotopic liver transplantation with extended cold ischemia time (18 h). Roles of CD4 T cells in the pathogenesis of IRI in liver allografts were determined using a depleting anti-CD4 antibody. The clinical relevance of CD4 as a marker of liver IRI was analyzed retrospectively in 55 liver transplant patients. Results: CD4 depletion in both donors and recipients resulted in the most effective protection of liver allografts from IRI, as measured by serum transaminase levels and liver histology. CD4 depletion inhibited IR-induced intragraft neutrophil/macrophage infiltration and proinflammatory gene expressions. Quantitative reverse-transcriptase polymerase chain reaction analysis of human liver biopsies (2 h postreperfusion) revealed that posttransplant, rather than pretransplant, CD4 transcript levels correlated positively with proinflammatory gene expression profile. When we divided patients into subgroups according to intragraft CD4 levels, the high CD4 cohort developed a more severe hepatocellular damage than that with low CD4 levels. Conclusions: CD4 T cells play a key pathogenic role in IRI of allogeneic liver transplants, and intragraft CD4 levels in the early postreperfusion phase may serve as a potential biomarker and therapeutic target to ameliorate liver IRI and improve orthotopic liver transplantation outcomes.